Le Frondeur : mensuel d'information de la communauté gay et lesbienne. (Paris : Before Communication, 1996)
Fonds Suzan Daniel (FSD)
Periodiciteit: maandelijks
Redactie: 7 rue Lucien Sampaix, 75010 Paris
Frans
Periodiek